High donor hemoglobin interacts with pre-transplant recipient neutropenia to modulate mortality after allogeneic hematopoietic stem cell transplantation: An exploratory, single-center, retrospective, real-world study - Mohammadreza Eslami; Mahdi Mehrabi; Mehrdad Payandeh (PLoS ONE, 2026)
Prognostication after allogeneic hematopoietic stem cell transplantation remains a critical challenge, and the complex interplay between recipient vulnerability and donor graft characteristics is poorly understood. The primary objective of this retrospective, hypothesis-generating study was to investigate the interaction between pre-transplant recipient neutropenia and donor hemoglobin levels on long-term survival. We performed a pragmatic, single-center, retrospective cohort study on 94 consecutive patients who underwent transplantation at a reference center in Western Iran. Using multivariable survival models, we assessed the independent and interactive effects of pre-transplant factors on 5-year overall survival, with appropriate handling of missing data. The robustness of our central finding was confirmed via sensitivity analyses. Our adjusted multivariable analysis revealed two main findings. First, higher continuous donor hemoglobin was associated with a trend toward increased mortality (Hazard Ratio per 1 g/dL increase = 1.45; 95% Confidence Interval, 0.87–2.39; p = 0.148). Second, the central finding was a statistically significant, qualitative interaction between recipient neutropenia and donor hemoglobin (adjusted HR = 0.44, p for interaction = 0.013). This interaction reversed the potentially deleterious effect of hemoglobin: in the subgroup of neutropenic recipients, higher donor hemoglobin was associated with a protective trend, mitigating the profoundly poor prognosis observed in patients with isolated neutropenia. In conclusion, our study identified a novel and statistically robust interaction, suggesting that the prognostic impact of donor hemoglobin is context-dependent and fundamentally altered by the recipient’s baseline immune status. While these preliminary findings provide a compelling rationale for future mechanistic studies, they require urgent validation in larger cohorts and should not be used to guide clinical donor selection.